1979
DOI: 10.1177/000456327901600126
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Assessment of Prolactin Status

Abstract: SUMMARYThe laboratory assessment of prolactin status was evaluated by detailed study of 921 subjects (587 normal subjects and 334 patients with pathological conditions). The effect on serum prolactin levels of age, sex, circadian rhythm, pulsatility of secretion, stress, drug ingestion, and pregnancy was defined in normal subjects. The normal prolactin responses to stimulation (TRH, metoclopramide) and suppression (t-dopa, bromocriptine) were also determined. Basal prolactin levels were measured in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

1982
1982
1993
1993

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 24 publications
3
25
1
Order By: Relevance
“…The sensitivity of the prolactin assay used in the study was comparable to those used by previous workers (Cowden et al, 1979;Stem et al, 1979). Basal values obtained in this study (between 10.00 and 11.00 h) were generally comparable with those reported previously (Frantz, 1977;Cowden et al, 1979).…”
Section: Bupropion Fails To Affect Plasma Prolactin and Growth Hormonsupporting
confidence: 81%
See 2 more Smart Citations
“…The sensitivity of the prolactin assay used in the study was comparable to those used by previous workers (Cowden et al, 1979;Stem et al, 1979). Basal values obtained in this study (between 10.00 and 11.00 h) were generally comparable with those reported previously (Frantz, 1977;Cowden et al, 1979).…”
Section: Bupropion Fails To Affect Plasma Prolactin and Growth Hormonsupporting
confidence: 81%
“…The sensitivity of the prolactin assay used in the study was comparable to those used by previous workers (Cowden et al, 1979;Stem et al, 1979). Basal values obtained in this study (between 10.00 and 11.00 h) were generally comparable with those reported previously (Frantz, 1977;Cowden et al, 1979). Since prolactin secretion during the night appears to be increased by sleep (Sassin et al, 1973) the best time for measurement of basal prolactin concentrations may depend on the circumstances of the particular study.…”
Section: Bupropion Fails To Affect Plasma Prolactin and Growth Hormonsupporting
confidence: 81%
See 1 more Smart Citation
“…Indeed such arguments have led to the suggestion (Jeffcoate, 1978) that serial blood sampling would be more advantageous in the estimation of prolactin status. However, a number of investigations have concluded that venepuncture rarely, if ever, induces prolactin release (Koninckx, 1978;Cowden et al, 1979;Pearce et al, 1980) and that frequent sampling does not improve the value of a result (Pearce et al, 1980;Moult et al, 1981 present report may be viewed with confidence. There are, however, a variety of drugs which can affect prolactin release (Fluckinger, 1972) and it is unfortunate that we were unable to take account of this.…”
Section: Discussionmentioning
confidence: 51%
“…The defined time period was chosen to avoid major variation due to the diurnal rhythm of prolactin. By 9.30 am, the fall of prolactin levels from their nocturnal, sleep-induced peak has reached a plateau (Cowden et al, 1979). It has been suggested that artefactual high prolactin levels may occur due to pulsatile release (Ehara et al, 1973) or stress at venepuncture (Koninckx, 1978).…”
Section: Discussionmentioning
confidence: 99%